Role of Apoptosis in Wound Healing and Apoptosis Alterations in Microgravity - Riwaldt, Stefan; Corydon, Thomas J.; Pantalone, Desiré; Sahana, Jayashree; Wise, Petra; Wehland, Markus; Krüger, Marcus; Melnik, Daniela; Kopp, Sascha; Infanger, Manfred; Grimm, Daniela (Frontiers in Bioengineering and Biotechnology, 2021)
Functioning as the outermost self-renewing protective layer of the human organism, skin protects against a multitude of harmful biological and physical stimuli. Consisting of ectodermal, mesenchymal, and neural crest-derived cell lineages, tissue homeostasis, and signal transduction are finely tuned through the interplay of various pathways. A health problem of astronauts in space is skin deterioration. Until today, wound healing has not been considered as a severe health concern for crew members. This can change with deep space exploration missions and commercial spaceflights together with space tourism. Albeit the molecular process of wound healing is not fully elucidated yet, there have been established significant conceptual gains and new scientific methods. Apoptosis, i.e., programmed cell death, enables orchestrated development and cell removal in wounded or infected tissue. Experimental designs utilizing microgravity allow new insights into the role of apoptosis in wound healing. Furthermore, impaired wound healing in unloading conditions would depict a significant challenge in human-crewed exploration class space missions. In this review, we provide an overview of alterations in the behavior of cutaneous cell lineages under microgravity in regard to the impact of apoptosis in wound healing. We discuss the current knowledge about wound healing in space and simulated microgravity with respect to apoptosis and available therapeutical strategies.